Dynamic impact of energy consumption, private investment and financial development on environmental pollutions: evidence from Malaysia - Hassan, Sallahuddin (EconJournals, 2018)
This study is aimed at exploring the impact of energy consumption, private investment, financial development and economic growth on carbon dioxide (CO2) emissions in Malaysia employing the autoregressive distributed lags model for the period 1976-2013. The result reveals the presence of long run association connecting the variables and established that private investment and energy consumption impact positively on CO2 emissions in Malaysia.For that reason, the study recommends the implementation of clean technology by private investors is essential in managing CO2 emissions in Malaysia.